2020
DOI: 10.1155/2020/8283401
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Key Biomarkers for Bladder Cancer: A Study Based on TCGA and GEO Data

Abstract: Bladder cancer (BLCA) is a common malignant cancer, and it is the most common genitourinary cancer in the world. The recurrence rate is the highest of all cancers, and the treatment of BLCA has only slightly improved over the past 30 years. Genetic and environmental factors play an important role in the development and progression of BLCA. However, the mechanism of cancer development remains to be proven. Therefore, the identification of potential oncogenes is urgent for developing new therapeutic directions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Consistent with our study, PDGFRA, AHNAK and RAC3 were risk factors, whereas OAS1 and SH3BP2 were protective factors. Another study revealed that DEG between bladder cancers and normal tissues were enriched in PDGF signaling and immune-related signalings ( 28 ). Moreover, PDGF signaling contributed to immune microenvironment and unfavorable prognosis in an analysis of multiple tumors ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, PDGFRA, AHNAK and RAC3 were risk factors, whereas OAS1 and SH3BP2 were protective factors. Another study revealed that DEG between bladder cancers and normal tissues were enriched in PDGF signaling and immune-related signalings ( 28 ). Moreover, PDGF signaling contributed to immune microenvironment and unfavorable prognosis in an analysis of multiple tumors ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis methods have been increasingly used in the medical field [ 14 , 15 ]. In this study, we used various bioinformatics methods to deeply study the potential role of pathways regulating immune responses in KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…With regarding to BLCA, many potential biomarkers were identi ed with bioinformatics, for example, CDC20, ASPM, TAGLN, ACTA2, MYH11, CALD1, MYLK, GEM, PRELP, TPM2, and OGN (15)(16)(17)(18)(19). In addition, several signaling pathways involved in BLCA, including vascular smooth muscle contraction, hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), focal adhesion, cGMP-PKG, cAMP, MAPK and PI3K-AKT, were screened out(15) , (16). However, most previous studies only used the cancer genome atlas (TCGA) database or Gene Expression Omnibus (GEO) database when WGCNA was applied (13,18).…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies only used the cancer genome atlas (TCGA) database or Gene Expression Omnibus (GEO) database when WGCNA was applied (13,18). Moreover, although there were studies based on TCGA and GEO database, only differential gene expression analysis was performed (16,17). It was the rst time to combine WGCNA with differential gene expression analysis to identify biomarkers of BLCA based on TCGA database and GEO database.…”
Section: Introductionmentioning
confidence: 99%